Efektivitas Penerapan Model Pembelajaran Role Playing Terhadap Hasil Belajar Siswa Pada Materi Sejarah Kebudayaan Islam - Erika Marianti; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2023)
The history of Islamic cultural history emphasizes to students the necessity to uphold noble and Islamic values, principles, attitudes to life in carrying out daily life. However, in reality, the teaching methods used by teachers are still monotonous, so students find it difficult to understand the material and have an impact on low student learning outcomes. So it is necessary to use appropriate and interesting learning models by teachers in the learning process. This study aims to look at the effectiveness of applying the role playing model to student learning outcomes in class V Islamic cultural history at SDN 52 Parupuk Tabing. The sampling technique in this study used purposive sampling. The data in the study were analyzed using a paired sample t-test. Then the effectiveness test was carried out, the value of R < 1 (0.30 < 1) was obtained so that it could be stated that the application of the role playing learning model was effective in improving student learning outcomes in class V on Islamic Cultural History material at SDN 52 Parupuk Tabing.